2011
DOI: 10.1097/jom.0b013e318237a14b
|View full text |Cite
|
Sign up to set email alerts
|

Are Occupational Factors and Mental Difficulty Associated With Occupational Injury?

Abstract: High-occupational demands and depressive symptoms can be early identified and monitored to prevent injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
1
31
1
Order By: Relevance
“…"Repeated injuries" was defined as two or more injuries. Similar questions have been used in adolescent and adult population studies (Bhattacherjee et al, 2013;Chau et al, 2008Chau et al, , 2011Hibell et al, 2004;Molcho et al, 2006).…”
Section: Single and Repeated School And Out-of-school Injuriesmentioning
confidence: 92%
See 1 more Smart Citation
“…"Repeated injuries" was defined as two or more injuries. Similar questions have been used in adolescent and adult population studies (Bhattacherjee et al, 2013;Chau et al, 2008Chau et al, , 2011Hibell et al, 2004;Molcho et al, 2006).…”
Section: Single and Repeated School And Out-of-school Injuriesmentioning
confidence: 92%
“…The results interpretation should be cautious as the 95% CIs of ORs were often overlapped. Various measures (socioeconomic factors, injuries, Table 4 Contribution of socioeconomic factors, school, behaviour and health-related difficulties to the associations between sleep difficulty and school and out-of-school single and repeated injuries (vs. none): odds ratio (OR), 95% confidence interval (CI) and contribution (% sleep difficulty, school performance, drug use, health status, psychological health, and involvement in violence) have been used in other studies (Bhattacherjee et al, 2013;Chau et al, 2008Chau et al, , 2011Hibell et al, 2004;Kandel and Davies, 1982;Leplège et al, 2000;Mayet et al, 2011;Molcho et al, 2006;Raphael et al, 2005;Skevington et al, 2004;Swanh et al, 2012). School performance and obesity were objective measures.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Although the majority of studies on depression have observed a significant association between depression and injury, one study did not find any such association, and some studies found that association existed among only men or women. Another study found that the strength of the association between depressive symptoms and risk of injury depended on the persistence of the symptoms 41) . Therefore, the mechanisms and causal links between burnout, health and injuries need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in issues such as newsqol domains prompts concern about the future in terms of consequences of stroke, daily living activities, desire for improvement and fear of aggravation [9]. Some newsqol domains reflect depressive symptoms, which are associated with injury, disability and premature death [10,11]. One study reported a risk of depression after stroke [12].…”
Section: Introductionmentioning
confidence: 99%